Consumer Search Ability, Price Dispersion and the Digital Divide1. (19th October 2016) - McDonald, Stephen; Wren, Colin
Abstract: The 'digital divide' in online activities is believed to arise from differences in Internet access, but this paper advances an alternative explanation that is related to consumer search ability. It argues that this leads to greater price dispersion, causing some consumers to be discriminated against. It analyses price data for the UK Internet motor insurance market, collecting data on 32, 255 prices for 110 sub‐markets, where differences in price dispersion across these by age, occupation and sex of the driver are argued to reflect differences in search ability. Allowing for price dispersion to also depend on the insurance risk, it finds greater price dispersion for consumers with weaker search abilities, i.e. older, unemployed, retired or female consumers. As this is not explained by alternative hypotheses, the paper concludes that improved Internet access alone will not close the 'digital divide'. The implication is that policymakers should address the online search abilities of individuals as well as Internet access.